Comparative transcriptomic analysis reveals novel roles of transcription factors and hormones during the flowering induction and floral bud differentiation in sweet cherry trees (Prunus avium L. Cv. Bing) - Villar, Luis (2020)
In sweet cherry trees, flowering is commercially important because the flowers, after fertilization, will generate the fruits. In P. avium, the flowering induction and flower organogensis are the first developmental steps towards flower formation and they occur within specialized organs known as floral buds during the summer, nine months before blooming. During this period the number of floral buds per tree and the bud fruitfulness (number of flowers per bud) are stablished affecting the potential yield of orchards and the plant architecture. The floral bud development is sensitive to any type of stress and the hotter and drier summers will interfere with this process and are calling for new adapted cultivars. A better understanding of the underlying molecular and hormonal mechanisms would be of help, but unlike the model plant Arabidopsis, very little is known about floral induction in sweet cherry. To explore the molecular mechanism of floral bud differentiation, high-throughput RNA sequencing was used to detect differences in the gene expression of P. avium floral buds at five differentiation stages. We found 2,982 differentially expressed genes during floral bud development. We identified genes associated with floral initiation or floral organ identity that appear to be useful biomarkers of floral development and several transcription factor families (ERF, MYB, bHLH, MADS-box and NAC gene family) with novel potential roles during floral transition in this species. We analyzed in deep the MADS-box gene family and we shed light about their key role during floral bud and organs development in P. avium. Furthermore, the hormonal-related signatures in the gene regulatory networks and the dynamic changes of absicic acid, zeatin and indolacetic acid contents in buds suggest an important role for these hormones during floral bud differentiation in sweet cherry. These data provide a rich source of novel informacion for functional and evolutionary studies about floral bud development in sweet cherry and new tools for biotechnology and breeding.